Crisis in Syria: Possibilities and limits of military intervention - Markus Kaim (Stiftung Wissenschaft und Politik (SWP), 2012)
Now that the opposition Syrian National Council has begun calling for international military intervention and an arms embargo, further military escalation of the crisis appears inevitable. This exacerbates the dilemma for international politics: Either Western governments accept the failure of their efforts to contain the conflict, and allow events to escalate into full-blown civil war with casualties running into the thousands. Or they weigh up the options for military engagement, with all the associated battlefield risks and political uncertainties
Keywords: 320